ЭВОЛЮЦИЯ ПОДХОДА К УПРАВЛЕНИЮ ПРОЕКТНЫМИ РИСКАМИ В СТАНДАРТЕ PMBOK GUIDE - Микаел Ншанян; Нелли Долмазян (World Science, 2019)
In the article, the evolution of project risk management processes in the six sequential editions of the PMBOK Guide standard, developed by the Project Management Institute (PMI), is analysed. Special attention is paid to the last edition of the PMBOK Guide standard. The PMI approach to the project risks management is compared with the outlooks of the other most well- known standards and methodologies of project management.